Ihmisen elämä ; Laulu maalle - Second Flash (yhtye); Autio, Juha; Kattilakoski, Kyösti; Kauppila, Hannu; Pouttu, Jarmo; Toivonen, Kalevi; Yli-Korpela, Juha (Second Flash, 1989)
2 kappaletta.
Keywords: Second Flash (yhtye) : singlet